Adaptasi Sosial Mahasiswa Asing PTKIN Sulawesi Selatan Perspektif Teori Praksis Pierre Bourdieu - Darussalam, Fajrul Ilmy; Andi Batara Indra; Saifur Rahman; Bunga Risa (Pascasarjana IAIN Metro, 2025)
This study aims to analyze the social adaptation strategies of foreign students of State Islamic Religious Universities in South Sulawesi through the perspective of Pierre Bourdieu's praxis theory. The research subjects are foreign students of PTKIN in South Sulawesi from UIN Alauddin Makassar and IAIN Palopo. This research prioritizes philosophical reflection on a problem, with an approach to the study of social philosophy using Pierre Bourdieu's theory of praxis. The stages begin with data collection, primary and secondary data grouping, research data systematization, and analysis of results. Data analysis uses methodological elements such as description, interpretation, internal coherence, and confirmability. The results are 1) foreign students of PTKIN in South Sulawesi generally experience several obstacles such as language barriers caused by the use of dialects and regional languages, differences in socio-cultural and religious conditions caused by various social norms and customary norms, to limited social networks caused by stereotypes and social assessments. 2) The social adaptation strategy is by forming the right habitus and using the right capital composition in certain fields. Higher education is a field that is being undertaken by foreign students. So, the habits that should be formed include an attitude of responsibility, diligence, discipline, never giving up and mutual respect. Meanwhile, some of the capital needed is strengthening Indonesian and English language skills as cultural capital, scholarship awards as economic capital, networking skills as social capital, and academic status as symbolic capital.